Identificação e caracterização de defeitos pontuais em nitreto de boro hexagonal induzidos por irradiação de nêutrons rápidos - José Roberto de Toledo (2021)
In the last years, the study of bidimensional semiconductors (2D) has attracted great interest aiming scientific and technological applications, because they are promising materials for the production of ultrafine and optoelectronic devices. As in 3D semiconductors, point defects even at low concentration, often control optical, electrical and catalytic properties of these materials. The electron paramagnetic resonance (EPR) and correlated advanced techniques represent a powerful tool to characterization and identification of intrinsic and extrinsic point defects. In this work, EPR is employed as the principal experimental technique in the study of point defects in monocrystalline and policrystalline hexagonal boron nitride (h-BN) samples induced by fast neutron irradiation. The experimental techniques of optical absorption spectroscopy, luminescence and Raman, in addition to X-ray diffraction and scanning electron microscopy, were used for the initial characterization of the samples. The immense interest in h-BN both exfoliated to the limit of a monolayer and in bulk, are related with the recent discover of single photon emission from intrinsic point defects in its crystalline structure at room temperature, evidencing it as a promising material for applications in quantum computation and correlated areas. In this work the characterization and identification of different radiation-induced defects is presented including the negatively charged boron vacancies (VB), nitrogen antisite next to nitrogen vacancies (VNNB), carbon impurities on nitrogen sites next to boron vacancies (CNVB), besides the characterization of a forth yet unknown defect. From the EPR measurements it was determined that the VB defect has high electronic spin S = 1, with g-factor approximately equal to 2 and fine constant interaction D = 3,5 GHz at room temperature with a correlated photoluminescence band in the near infrared. The other defects also shown g-factors in the close vicinity of g = 2, however presenting electronic spin S = 1/2 and axial hyperfine interactions of magnitude of the order of 10 to 100 MHz. All studied defects present good thermal stability, with its paramagnetic states persisting to thermal treatments up to 500 °C and for specific cases up to 850 °C. After thermal treatment, the samples were also exposed to gamma irradiation from a source of 60Co to verify whether the defects were annihilated. Simulations of the observed EPR spectra and analysis of theoretical models available in the literature were used to identify the defects produced by neutron irradiation.